Screening of bael (Aegle marmelos Correa) cultivars for preparation of candy (Indian Journal of Arid Horticulture, 2025)
Bael (Aegle marmelos Correa) is an importance indigenous fruit of rutaceae family. The tree is very hardy in nature and can withstand against various biotic and abiotic stresses. The importance of bael is enumerated in ancient Indian and Buddhist literature. The fruits of bael is known for its curative properties and nutritive value. The fruit pulp contains fair amount of vitamin A, C and high amount of riboflavin (Gopalan et al., 1985 and Saroj et.al., 2006). The fruit pulp contains marmelosin, which is laxative, diuretic, astringent, digestive, stomachic and also posses anti-amoebic and hypoglycemic properties.
Keywords: indigenous; enumerated; astringent; diuretic; marmelosin; hypoglycemic